Paper 32: All-inside meniscus repair leads to higher rate of failure compared to inside-out meniscus repair in elite athletes. Issue 7 (30th July 2022) - Webster, Emily; Jones, Mary; Williams, Andy; Borque, Kyle
Objectives: The popularization of 'all-inside' meniscal repair devices has led to a paradigm shift away from the historical gold standard of 'inside-out' meniscus repair but without comparative studies to support the change. The purpose of this study was to compare the failure rate of 'all-inside' and 'inside-out' meniscus repair performed in elite athletes. Methods: A retrospective review was performed of all professional or national/international level amateur athletes who underwent meniscal repair between January 1, 2013 and December 31, 2018, with a minimum of two year follow-up. Repairs were classified as 'all-inside' or 'inside-out' depending on the type of repair performed. Failure was defined as undergoing a subsequent surgery to address a persistent meniscal tear following repair. Results: 158 (106 lateral and 52 medial) meniscal repairs were performed on elite athletes during this time period. Overall, 38 out of 158 (24.1%) underwent subsequent meniscectomy or revision meniscal repair. 27 of 88 (30.7%) of 'all-inside' meniscal repairs failed versus 11 of 70 (15.7%) of 'inside-out' meniscal repairs (p=0.029). For medial meniscus repairs, 'all-inside' failed at a higher rate than 'inside-out' medial meniscus repairs (58.6% vs 26.1%. p=0.019) but no statistical difference was found in lateral meniscus repairs (16.9% vs 10.6%, p=0.354). Overall 23 out of 52 (44.2%) of medial meniscus repairs failed compared to 15 of 106 (14.2%) of lateral meniscus repairs (p=0.00003) Cruciate ligament reconstruction was performed at the same time with 27 of 29 'all-inside' medial meniscus repairs, 21 of 23 'inside-out' medial meniscus repairs, 45 of 59 'all-inside' lateral meniscus repairs but only 18 of 47 'inside-out' lateral meniscal repairs. Conclusions: 'All-inside' meniscal repair led to a higher rate of failure compared to 'inside-out' meniscus repair in elite athletes. Medial meniscus repairs failed at a high rate than lateral meniscal repairs. This difference is even more noteworthy considering that only a minority of inside out lateral meniscal repairs were done in conjunction with a cruciate ligament reconstruction versus the majority of the other three groups studied. Due to the increased knee loading in elite sports, clinically relevant differences between the medial and lateral meniscus as well as repair strategies were elucidated that may not be in the general population. UPLOAD-https://planion-client-files.s3.amazonaws.com/AOSSM/blobs/fb465a3d-3b0f-451f-8fad-0d1332b8b428/1/Meniscal_repair_chart.docx None None None